Polypyrrole coating, preparation method of polypyrrole coating, composite copper foil for circuit and preparation method of composite copper foil
By using polypyrrole coating and precious metal nanoparticles in the composite copper foil, composite copper foil with higher conductivity and mechanical strength is solved, and the production cost is reduced. Achieve more efficient industrial mass production.
Patent Information
- Application Number
- CN202411299963.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing composite copper foils have shortcomings in improving conductivity, mechanical strength and electrochemical properties, and the addition of colloidal solutions of precious metal salts increases production costs and affects industrial mass production.
A polypyrrole coating is adopted, including multi-walled carbon nanotubes and precious metal nanoparticles. The composite copper foil is formed by forming a polypyrrole coating on a polymer base film and electroless copper plating thereon.
The conductive properties and mechanical strength of composite copper foil are improved, and the brittleness and deformation problems in high-temperature environments are solved, while reducing production costs and achieving more efficient industrial preparation.
Smart Images

Figure CN119192988A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic materials, and in particular relates to a polypyrrole coating, a preparation method thereof, a composite copper foil for circuits and a preparation method thereof. Background Art
[0002] Flexible copper clad laminate (FCCL) adopts a three-layer structure, including polyimide (PI) film, adhesive and copper foil. Or it adopts a double-layer adhesive-free structure, that is, the PI film is prepared by polymerization on the surface of copper foil. This structure can maintain good conductive properties while meeting the equipment's requirements for flexibility and reliability. By applying FCCL, electronic devices can adapt to various scenarios more flexibly and provide a better user experience.
[0003] Resin composite copper foil is a combination of metal conductor copper and polymer film or substrate as the basic structure. Composite copper foil with conductor copper only on one side of the polymer film or substrate is called single-sided composite copper foil; composite copper foil with conductor copper on both sides of the polymer film or substrate is called double-sided composite copper foil. At present, resin composite copper foil can be used for the production of display touch sensors (metal grids), printed circuit boards, etc.; it can also be used in the field of new energy batteries as a composite current collector. Compared with traditional current collectors, composite current collectors have the advantages of low manufacturing cost, high safety, strong compatibility, etc. Batteries using composite current collectors have high energy density and long cycle life.
[0004] Chinese invention patent application CN118064945A discloses a resin composite copper foil and a preparation method thereof, the preparation method comprising the following steps: coating a photocurable resin coating on a primer layer or on a polymer substrate surface and drying the coating, then coating a palladium acetate or palladium chloride activated colloidal solution and drying the coating; performing exposure curing to form an activated photocurable resin layer, performing chemical copper plating on the surface of the activated photocurable resin layer to form a copper seed layer, and forming a copper plating layer of a certain thickness on the surface of the copper seed layer by water electroplating. The resin copper foil obtained by the invention has excellent bonding strength and extremely small surface roughness, and is suitable for preparing display sensors and high-density printed circuit boards containing fine circuits. However, the addition amount of the precious metal salt colloidal solution of the invention is relatively high, which will increase the cost in the production process and is not conducive to industrial mass production.
[0005] Another Chinese invention patent application, CN117777522A, discloses a composite copper foil for flexible circuits, its preparation method and application. The invention embeds a layer of polyaniline conductive polymer between the flexible polymer substrate and the copper foil, which not only maintains the flexibility of the composite copper foil, but also enhances its conductivity. The traditional thermosetting resin is replaced by polyaniline, which effectively prevents the deformation and delamination of the circuit board caused by the deterioration of the adhesive at high temperature. In addition, the use of precious metal particles provides conditions for the chemical copper plating step, simplifies the necessary substrate processing steps, such as roughening, impregnation, tin sensitization and activation, and makes the entire process operation simpler. However, polyaniline may lead to poor adhesion between the copper foil and the substrate, and the thermal stability and chemical resistance of polyaniline may not be as good as resin, which may affect the service life and performance stability of the copper foil.
[0006] In view of this, there is an urgent need in the art to develop a composite copper foil that can comprehensively improve electrical conductivity, mechanical strength and electrochemical properties. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a polypyrrole coating, a preparation method thereof, a composite copper foil for circuits and a preparation method thereof.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A polypyrrole coating comprises polypyrrole, multi-walled carbon nanotubes and noble metal nanoparticles distributed in the polypyrrole.
[0010] Preferably, the noble metal is selected from one or more of palladium, silver, ruthenium, platinum, iridium and gold.
[0011] More preferably, the noble metal is palladium.
[0012] The present invention also provides a method for preparing the polypyrrole coating, comprising the following steps:
[0013] (1) dissolving a noble metal salt in an acidic medium, and sequentially adding a polyol, a steric stabilizer, and a reducing agent to obtain a dispersion containing noble metal nanoparticles;
[0014] (2) In situ polymerization of pyrrole in an acidic medium containing multi-walled carbon nanotubes, a dispersion containing precious metal nanoparticles, a steric stabilizer and an oxidant to obtain the polypyrrole coating.
[0015] Preferably, the noble metal salt in step (1) is a noble metal acetate or a noble metal chloride.
[0016] Preferably, the steric stabilizer in step (1) is selected from one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyvinyl pyrrolidone.
[0017] More preferably, the steric stabilizer is sodium dodecylbenzene sulfonate or sodium dodecyl sulfate.
[0018] Preferably, the acidic medium in step (1) is selected from one or more of hydrochloric acid, nitric acid and sulfuric acid.
[0019] More preferably, the acidic medium is hydrochloric acid.
[0020] Preferably, the concentration of the acidic medium is 1-4M.
[0021] More preferably, the concentration of the acidic medium is 3-4M.
[0022] Preferably, the polyol in step (1) is selected from one or more of ethylene glycol, propylene glycol, n-butanol, isobutanol, 1,4-butanediol, 1,5-pentanediol and cyclohexanol.
[0023] More preferably, the polyol is ethylene glycol, 1,4-butanediol or 1,5-pentanediol.
[0024] Preferably, the reducing agent in step (1) is a sodium bisulfite solution with a concentration of 70-90 mM.
[0025] Preferably, the process of sequentially adding the polyol, the steric stabilizer and the reducing agent in step (1) comprises first adding the polyol preheated to 100-120°C, stirring for 2-4h, then adding the steric stabilizer, keeping warm at 100-120°C and stirring for 0.5-1.5h, and finally adding the reducing agent, keeping warm at 100-120°C and stirring for 0.5-1h, centrifuging, washing with water, and ultrasonicating to obtain the product.
[0026] Preferably, the mass volume ratio of the noble metal salt, steric stabilizer, reducing agent and polyol in step (1) is 1g:2-4g:2-6ml:180-300ml.
[0027] Preferably, the concentration of the noble metal nanoparticles in the solution in step (1) is 0.16-0.4 mmol / ml.
[0028] Preferably, the oxidant in step (2) is ammonium persulfate.
[0029] Preferably, the mass volumes of the pyrrole, multi-walled carbon nanotubes, dispersion containing precious metal nanoparticles, steric stabilizer, oxidant and acidic medium in step (2) are 2-4 g: 0.004-0.01 g: 1.25-10 ml: 10-20 g: 40-70 g: 4-10 ml.
[0030] Preferably, the in-situ polymerization is carried out under ice-water bath conditions.
[0031] The present invention also provides the use of the polypyrrole coating or the polypyrrole coating prepared by the above preparation method in preparing a composite copper foil for circuits.
[0032] The present invention also provides a composite copper foil for circuits, comprising the above-mentioned polypyrrole coating or the polypyrrole coating prepared by the above-mentioned preparation method, a polymer base film, a cured resin coating, a noble metal colloid coating and a copper layer; one side or both sides of the polymer base film are the cured resin coating, the noble metal colloid coating, the polypyrrole coating and the copper layer, and the surface of the polypyrrole coating away from the polymer base film is the copper layer.
[0033] The present invention also provides a method for preparing the composite copper foil, comprising the following steps:
[0034] (1) first coating the surface of the polymer base film with a light-curable resin coating, and then immersing it in the above-mentioned polypyrrole coating or the polypyrrole coating prepared by the above-mentioned preparation method to obtain a polymer composite film;
[0035] (2) The polymer composite film is then immersed in an alkaline chemical copper plating solution for copper plating to obtain a composite copper foil.
[0036] The invention coats a light-curing resin coating on a polymer substrate, thereby significantly increasing the adhesion of the composite copper foil.
[0037] Preferably, the polymer base film in step (1) is selected from any one of polyimide film, polypropylene film, polyvinyl chloride film, polystyrene film, polyphenylene sulfide film, polybutylene terephthalate film, poly(p-phenylene terephthalamide), polypropylene film, butadiene-styrene copolymer film, polyimide film, imide film, polyethylene terephthalate film, polyethylene PE film, polypropylene PP film, polyethylene phthalate PET film and polybutylene phthalate PBT film.
[0038] More preferably, the polymer base film is ethylene PE film, polypropylene PP film, polyethylene phthalate PET film or polybutylene phthalate PBT film.
[0039] Preferably, the coating dry weight of the coating in step (1) is 0.1-6 g / cm 3 .
[0040] Preferably, the polymer composite film in step (1) needs to be exposed and cured, and the thickness of the polymer composite film is 60-100 nm.
[0041] Preferably, the alkaline chemical copper plating solution in step (2) is composed of copper sulfate with a concentration of 5-10 g / L, sodium hypophosphite with a concentration of 10-30 g / L, dimethylaminoborane with a concentration of 0.5-2.0 g / L, and disodium ethylenediaminetetraacetate with a concentration of 15-20 g / L.
[0042] Preferably, the copper plating temperature in step (2) is 80-100° C., and the copper plating time is 1-2 h.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) The present invention adds a layer of conductive polymer polypyrrole between the polymer base film and the copper foil, thereby improving the conductivity while ensuring the flexibility of the composite copper foil; adding multi-walled carbon nanotubes to the polypyrrole coating can improve the conductive properties of the copper foil and effectively solve the problem of copper foil becoming brittle and deforming in a high temperature environment.
[0045] (2) The present invention adds precious metal particles to the polypyrrole coating to improve the conductivity of the copper foil; by adding a steric stabilizer, the mechanical strength of the polypyrrole is enhanced, thereby promoting the improvement of the overall performance of the composite copper foil.
[0046] (3) The method for preparing pyrrole coating and composite copper foil of the present invention has the advantages of strong substrate adaptability, simple process, continuity, high efficiency, etc., is easier to achieve large-scale preparation, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a structural diagram of double-sided composite copper foil.
[0048] Figure 2 This is a structural diagram of single-sided composite copper foil.
[0049] Figure numerals: 1. polymer base film; 2. cured resin coating; 3. precious metal colloid coating; 4. polypyrrole coating; 5. copper layer. DETAILED DESCRIPTION
[0050] It is worth noting that the raw materials used in the present invention are all common commercially available products: photocurable resin, model U-CURE 9301, purchased from Kunshan Custer Polymer Materials Co., Ltd.; multi-walled carbon nanotubes, model XFM-70, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; hydrochloric acid, AR, purchased from Nanjing Chemical Reagent.
[0051] Example 1
[0052] A double-sided composite copper foil (structure such as Figure 1 As shown in the figure, it is composed of a polymer base film 1, a cured resin coating 2, a noble metal colloid coating 3, a polypyrrole coating 4 and a copper layer 5. The coatings on both sides of the polymer base film 1 are consistent, and the single side is sequentially composed of the cured resin coating 2, the noble metal colloid coating 3, the polypyrrole coating 4 and the copper layer 5, and the surface of the polypyrrole coating 4 away from the polymer base film 1 is the copper layer 5.
[0053] The preparation method is as follows:
[0054] (1) Pretreatment of polyethylene phthalate (PET) film: Prepare a film containing Ba(OH) 2 and NaHCO 3 A propylene glycol aqueous solution, wherein Ba(OH) 2 The concentration is 2M, NaHCO 3 The concentration is 0.5M, and the volume ratio of glycerol to water is 2:1. The polyethylene phthalate (PET) film is immersed in the solution for 3 hours and then dried. The treated PET film is coated with a light-curing resin coating and dried. The dry weight of the light-curing resin coating is 0.4g / cm 3 , the coating thickness is 60nm.
[0055] (2) Preparation of a solution containing palladium nanoparticles: Weigh 1.0771 g of palladium acetate, dissolve it in 4 ml of 3M hydrochloric acid, and then dilute it to 120 ml with deionized water to prepare a precious metal precursor solution. Heat 190 ml of ethylene glycol to 110°C in advance, stir and heat for 3 h, then slowly inject 10 ml of the precious metal precursor solution; then add sodium dodecylbenzene sulfonate (the mass ratio of sodium dodecylbenzene sulfonate to palladium is 2) and heat for 1 h; finally, add 4 ml of 80 mM sodium bisulfite and heat for 30 min to obtain a solution containing palladium nanoparticles, separate it by high-speed centrifuge, wash it with alcohol and water, and disperse it into 10 ml of dispersion by ultrasonic.
[0056] (3) Preparation of in-situ polymerization reaction solution: 2.684 g (40 mmol) of pyrrole, 10 ml of palladium nanoparticle dispersion obtained in step (2) (containing 0.4 mmol of palladium nanoparticles), 45.64 g of ammonium persulfate, 0.0048 g (1 mol) of multi-walled carbon nanotubes and 10 g of sodium dodecylbenzene sulfonate were added to 4 ml of 4M hydrochloric acid solution, and stirred evenly in an ice-water bath to prepare an in-situ polymerization reaction solution.
[0057] (4) In-situ polymerization: Immerse the pretreated PET film obtained in step (1) in the in-situ polymerization reaction solution, and stop the reaction when the color of the solution gradually changes from light purple to dark green. Take out the treated film, rinse it with hydrochloric acid, soak it in deionized water for 5 minutes, and dry it to obtain a Pd-PPy-PET-PPy-Pd film.
[0058] (5) Chemical copper plating: first, wash the Pd-PPy-PET-PPy-Pd film three times with ethanol to remove impurities; then, add 1 g of copper sulfate, 3 g of sodium hypophosphite, 0.2 g of dimethylaminoborane, and 2 g of EDTA-2Na to 120 ml of deionized water, and stir until completely dissolved to obtain an alkaline chemical copper plating solution; finally, immerse the Pd-PPy-PET-PPy-Pd film in the alkaline chemical copper plating solution, and copper plate it at 80°C for 1 hour to obtain a composite copper foil.
[0059] (6) Anti-oxidation treatment: The composite copper foil was immersed in an anti-oxidation solution (a mixed solution of 1.3 g / L benzoic acid and 1.3 g / L benzotriazole) for 8 seconds, the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.
[0060] Example 2
[0061] A single-sided composite copper foil (structure such as Figure 2 As shown), it is composed of a polymer base film 1, a cured resin coating 2, a precious metal colloid coating 3, a polypyrrole coating 4 and a copper layer 5; a single side of the polymer base film 1 is sequentially provided with a cured resin coating 2, a precious metal colloid coating 3, a polypyrrole coating 4 and a copper layer 5, and the surface of the polypyrrole coating 4 away from the polymer base film 1 is a copper layer 5.
[0062] The preparation method is as follows:
[0063] The same as Example 1, the only difference is that in step (4), the pretreated polyethylene phthalate (PET) film is floated in the in-situ polymerization reaction solution.
[0064] Example 3
[0065] A double-sided composite copper foil (structure such as Figure 1 As shown in the figure, it is composed of a polymer base film 1, a cured resin coating 2, a noble metal colloid coating 3, a polypyrrole coating 4 and a copper layer 5. The coatings on both sides of the polymer base film 1 are consistent, and the single side is sequentially composed of the cured resin coating 2, the noble metal colloid coating 3, the polypyrrole coating 4 and the copper layer 5, and the surface of the polypyrrole coating 4 away from the polymer base film 1 is the copper layer 5.
[0066] The preparation method is as follows:
[0067] (1) Pretreatment of polyethylene phthalate (PET) film: Prepare a film containing Ba(OH ) 2 and NaHCO 3 A propylene glycol aqueous solution, wherein Ba(OH) 2 The concentration is 1M, NaHCO 3The concentration is 0.1M, and the volume ratio of glycerol to water is 1:1. The polyethylene phthalate (PET) film is immersed in the solution for 3 hours and then dried. The treated PET film is coated with a light-curing resin coating and dried. The dry weight of the light-curing resin coating is 0.6g / cm 3 , the coating thickness is 60nm.
[0068] (2) Preparation of a solution containing palladium nanoparticles: Weigh 1.0771 g of palladium acetate, dissolve it in 4 ml of 3M hydrochloric acid, and then dilute it to 120 ml with deionized water to prepare a precious metal precursor solution. Heat 190 ml of ethylene glycol to 110°C in advance, stir and heat for 3 h, then slowly inject 5 ml of the precious metal precursor solution; then add sodium dodecylbenzene sulfonate (the mass ratio of sodium dodecylbenzene sulfonate to palladium is 2) and heat for 1 h; finally, add 4 ml of 80 mM sodium bisulfite and heat for 30 min to obtain a solution containing palladium nanoparticles, separate it by high-speed centrifuge, wash it with alcohol and water, and disperse it into 10 ml of dispersion by ultrasonic.
[0069] (3) Preparation of in-situ polymerization reaction solution: 2.684 g (40 mmol) of pyrrole, 5 ml of palladium nanoparticle dispersion obtained in step (2) (containing 0.2 mmol of palladium nanoparticles), 45.64 g of ammonium persulfate, 0.0048 g (1 mol) of multi-walled carbon nanotubes and 10 g of sodium dodecylbenzene sulfonate are added to 4 ml of 4M hydrochloric acid solution, and stirred evenly in an ice-water bath to prepare an in-situ polymerization reaction solution.
[0070] (4) In-situ polymerization: Immerse the pretreated PET film obtained in step (1) in the in-situ polymerization reaction solution, and stop the reaction when the color of the solution gradually changes from light purple to dark green. Take out the treated film, rinse it with hydrochloric acid, soak it in deionized water for 5 minutes, and dry it to obtain a Pd-PPy-PET-PPy-Pd film.
[0071] (5) Chemical copper plating: first use ethanol to clean the Pd-PPy-PET-PPy-Pd film three times to remove impurities; then take 0.6g of copper sulfate, 1.2g of sodium hypophosphite, 0.06g of dimethylaminoborane, and 1.8g of EDTA-2Na and add them to 120ml of deionized water, stir and mix until completely dissolved to obtain an alkaline chemical copper plating solution; finally, immerse the Pd-PPy-PET-PPy-Pd film in the alkaline chemical copper plating solution, and copper plate it at 80°C for 1h to obtain a composite copper foil.
[0072] (6) Anti-oxidation treatment: The composite copper foil was immersed in an anti-oxidation solution (a mixed solution of 1.3 g / L benzoic acid and 1.3 g / L benzotriazole) for 8 seconds, the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.
[0073] Example 4
[0074] A double-sided composite copper foil (structure such as Figure 1 As shown in the figure, it is composed of a polymer base film 1, a cured resin coating 2, a noble metal colloid coating 3, a polypyrrole coating 4 and a copper layer 5. The coatings on both sides of the polymer base film 1 are consistent, and the single side is sequentially composed of the cured resin coating 2, the noble metal colloid coating 3, the polypyrrole coating 4 and the copper layer 5, and the surface of the polypyrrole coating 4 away from the polymer base film 1 is the copper layer 5.
[0075] The preparation method is as follows:
[0076] (1) Pretreatment of polyethylene phthalate (PET) film: Prepare a film containing Ba(OH ) 2 and NaHCO 3 A propylene glycol aqueous solution, wherein Ba(OH) 2 The concentration is 1M, NaHCO 3 The concentration is 0.1M, and the volume ratio of glycerol to water is 1:1. The polyethylene terephthalate (PET) film is immersed in the solution for 3 hours and then dried. The treated PET film is coated with a light-curing resin coating and dried. The dry weight of the light-curing resin coating is 0.1g / cm 3 , the coating thickness is 60nm.
[0077] (2) Preparation of a solution containing palladium nanoparticles: Weigh 1.0771 g of palladium acetate, dissolve it in 4 ml of 3M hydrochloric acid, and then dilute it to 120 ml with deionized water to prepare a precious metal precursor solution. Heat 180 ml of ethylene glycol to 100°C in advance, stir and heat for 2 h, then slowly inject 1.25 ml of the precious metal precursor solution; then add sodium dodecylbenzene sulfonate (the mass ratio of sodium dodecylbenzene sulfonate to palladium is 2) and heat for 1.5 h; finally, add 6 ml of 70 mM sodium bisulfite and heat for 30 min to obtain a solution containing palladium nanoparticles, separate it by high-speed centrifuge, wash it with alcohol and water, and disperse it into 10 ml of dispersion by ultrasonic.
[0078] (3) Preparation of in-situ polymerization reaction solution: 2.684 g (40 mmol) of pyrrole, 1.25 ml of palladium nanoparticle dispersion obtained in step (2) (containing 0.2 mmol of palladium nanoparticles), 45.64 g of ammonium persulfate, 0.0048 g (1 mol) of multi-walled carbon nanotubes and 10 g of sodium dodecylbenzene sulfonate were added to 4 ml of 4M hydrochloric acid solution, and stirred evenly in an ice-water bath to prepare an in-situ polymerization reaction solution.
[0079] (4) In-situ polymerization: Immerse the pretreated PET film obtained in step (1) in the in-situ polymerization reaction solution, and stop the reaction when the color of the solution gradually changes from light purple to dark green. Take out the treated film, rinse it with hydrochloric acid, soak it in deionized water for 5 minutes, and dry it to obtain a Pd-PPy-PET-PPy-Pd film.
[0080] (5) Chemical copper plating: first use ethanol to clean the Pd-PPy-PET-PPy-Pd film three times to remove impurities; then take 1.2g of copper sulfate, 3.6g of sodium hypophosphite, 0.24g of dimethylaminoborane, and 2.4g of EDTA-2Na and add them to 120ml of deionized water, stir and mix until completely dissolved to obtain an alkaline chemical copper plating solution; finally, immerse the Pd-PPy-PET-PPy-Pd film in the alkaline chemical copper plating solution, and copper plate it at 80°C for 1h to obtain a composite copper foil.
[0081] (6) Anti-oxidation treatment: The composite copper foil was immersed in an anti-oxidation solution (a mixed solution of 1.3 g / L benzoic acid and 1.3 g / L benzotriazole) for 8 seconds, the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.
[0082] Example 5
[0083] A double-sided composite copper foil (structure such as Figure 1 As shown in the figure, it is composed of a polymer base film 1, a cured resin coating 2, a noble metal colloid coating 3, a polypyrrole coating 4 and a copper layer 5. The coatings on both sides of the polymer base film 1 are consistent, and the single side is sequentially composed of the cured resin coating 2, the noble metal colloid coating 3, the polypyrrole coating 4 and the copper layer 5, and the surface of the polypyrrole coating 4 away from the polymer base film 1 is the copper layer 5.
[0084] The preparation method is as follows:
[0085] (1) Pretreatment of polypropylene PP film: Prepare a film containing Ba(OH ) 2 and NaHCO 3 A propylene glycol aqueous solution, wherein Ba(OH) 2 The concentration is 1M, NaHCO 3 The concentration is 0.1M, and the volume ratio of glycerol to water is 1:1. The polypropylene PP film is immersed in the solution for 3 hours and then dried. The treated PP film is coated with a light-curing resin coating and dried. The dry weight of the light-curing resin coating is 0.1g / cm 3 , the coating thickness is 100nm.
[0086] (2) Preparation of a solution containing ruthenium nanoparticles: Weigh 1.0635 g of ruthenium acetate, dissolve it in 4 ml of 3M hydrochloric acid, and then dilute it to 120 ml with deionized water to prepare a precious metal precursor solution. Heat 300 ml of ethylene glycol to 120°C in advance, stir and heat for 4 hours, then slowly inject 1.25 ml of the precious metal precursor solution; then add sodium dodecyl sulfate (the mass ratio of sodium dodecyl sulfate to palladium is 4) and heat for 0.5 hours; finally, add 2 ml of 90 mM sodium bisulfite and heat for 60 minutes to obtain a solution containing ruthenium nanoparticles, separate it by high-speed centrifuge, wash it with alcohol and water, and disperse it into 10 ml of dispersion by ultrasonic.
[0087] (3) Preparation of in-situ polymerization reaction solution: 4.025 g (60 mmol) of pyrrole, 1.25 ml of ruthenium nanoparticle dispersion obtained in step (2) (containing 0.2 mmol of ruthenium nanoparticles), 68.45 g of ammonium persulfate, 0.0096 g (2 mol) of multi-walled carbon nanotubes and 20 g of sodium dodecylbenzene sulfonate are added to 10 ml of 4 M hydrochloric acid solution, and stirred evenly in an ice-water bath to prepare an in-situ polymerization reaction solution.
[0088] (4) In-situ polymerization: The pretreated PP film obtained in step (1) is immersed in the in-situ polymerization reaction solution. When the color of the solution gradually changes from light purple to dark green, the reaction is stopped. The treated film is taken out, rinsed with hydrochloric acid, and immersed in deionized water for 5 minutes, and dried to obtain a Ru-PPy-PP-PPy-Ru film.
[0089] (5) Chemical copper plating: first, use ethanol to clean the Ru-PPy-PP-PPy-Ru film three times to remove impurities; then take 1g of copper sulfate, 3g of sodium hypophosphite, 0.2g of dimethylaminoborane, and 2g of EDTA-2Na and add them to 120ml of deionized water, stir and mix until completely dissolved, and obtain an alkaline chemical copper plating solution; finally, immerse the Ru-PPy-PP-PPy-Ru film in the alkaline chemical copper plating solution, and copper plate it at 80°C for 1h to obtain a composite copper foil.
[0090] (6) Anti-oxidation treatment: The composite copper foil was immersed in an anti-oxidation solution (a mixed solution of 1.3 g / L benzoic acid and 1.3 g / L benzotriazole) for 8 seconds, the liquid was squeezed out by a water-collecting roller, dried by hot air at 100°C, and rolled up.
[0091] Comparative Example 1
[0092] A common commercially available double-sided flexible copper clad laminate was used as a control (wherein the thickness of the polyethylene phthalate (PET) film was 15 μm and the thickness of the adhesive layer was 3 μm).
[0093] Comparative Example 2
[0094] The same as Example 1, the only difference is that the pyrrole in step (3) is replaced by thiophene of equal molar mass.
[0095] Comparative Example 3
[0096] The same as Example 1, the only difference is that the palladium acetate in step (2) is replaced by zinc acetate of equimolar mass.
[0097] Comparative Example 4
[0098] Compared with Example 1, the only difference is that the polypyrrole coating does not contain palladium nanoparticles, that is, step (2) is omitted, and 2.684 g (40 mmol) of pyrrole, 10 ml of palladium nanoparticle dispersion obtained in step (2) (containing 0.4 mmol of palladium nanoparticles), 45.64 g of ammonium persulfate, 0.0048 g (1 mol) of multi-walled carbon nanotubes and 10 g of sodium dodecylbenzene sulfonate are directly added to 4 ml of 4M hydrochloric acid solution, stirred evenly in an ice-water bath, and prepared into an in-situ polymerization reaction solution.
[0099] Comparative Example 5
[0100] The same as Example 1, the only difference is that in step (2), 25 ml of 70 mM sodium bisulfite is added during the reduction of the metal salt.
[0101] Comparative Example 6
[0102] The same as Example 1, the only difference is that in step (2), 4 ml of 120 mM sodium bisulfite is added during the reduction of the metal salt.
[0103] Test Case
[0104] Performance test of composite copper foil:
[0105] (1) The thickness of the copper foil layer of the composite copper foil prepared in the above embodiments and comparative examples was measured using a step profiler.
[0106] (2) The adhesion between the film and the substrate was evaluated using the 100-grid method. Referring to GB / T9286-2021 “Scratching test for paint and varnish films”, a multi-blade cutting knife was used to cut 6 parallel slits on the sample surface, with the interval between each slit being 2 mm.
[0107] (3) The resistivity was measured using the four-probe method.
[0108] (4) According to the test requirements of the national standard GB / T1355, the sample was cut into a size of 25 mm × 100 mm and the peel strength was tested using a SANS electronic universal testing tensile machine. The vertical moving speed of the tensile module of the tensile machine was set to 10 mm / min.
[0109] The performance test results of the composite copper foil prepared in each embodiment and comparative example are shown in Table 1.
[0110] Table 1 Composite copper foil performance characterization results
[0111]
[0112]
[0113] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A polypyrrole coating, characterized in that: The polypyrrole coating comprises polypyrrole, multi-walled carbon nanotubes and noble metal nanoparticles distributed in the polypyrrole.
2. The polypyrrole coating according to claim 1, characterized in that The noble metal is selected from one or more of palladium, silver, ruthenium, platinum, iridium and gold.
3. A method for preparing a polypyrrole coating as claimed in claim 1 or 2, characterized in that: The steps include: (1) dissolving a noble metal salt in an acidic medium, and sequentially adding a polyol, a steric stabilizer, and a reducing agent to obtain a dispersion containing noble metal nanoparticles; (2) In situ polymerization of pyrrole in an acidic medium containing multi-walled carbon nanotubes, a dispersion containing precious metal nanoparticles, a steric stabilizer and an oxidant to obtain the polypyrrole coating.
4. The preparation method according to claim 3, characterized in that: The noble metal salt in step (1) is a noble metal acetate or a noble metal chloride, the acidic medium is selected from one or more of hydrochloric acid, nitric acid and sulfuric acid, the concentration of the acidic medium is 1-4M, the polyol is selected from one or more of ethylene glycol, glycerol, n-butanol, isobutanol, 1,4-butanediol, 1,5-pentanediol and cyclohexanol, the steric stabilizer is selected from one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate and polyvinyl pyrrolidone, and the reducing agent is a sodium bisulfite solution with a concentration of 70-90mM.
5. The preparation method according to claim 4, characterized in that: The process of sequentially adding the polyol, the steric stabilizer and the reducing agent in step (1) comprises first adding the polyol preheated to 100-120° C., stirring for 2-4 hours, then adding the steric stabilizer, keeping warm at 100-120° C. and stirring for 0.5-1.5 hours, and finally adding the reducing agent, keeping warm at 100-120° C. and stirring for 0.5-1 hour, centrifuging, washing with water, and ultrasonicating to obtain a product having a mass volume ratio of the noble metal salt, the steric stabilizer, the reducing agent and the polyol of 1g:2-4g:2-6ml:180-300ml, and a concentration of the noble metal nanoparticles in the dispersion of 0.16-0.4mmol / ml.
6. The preparation method according to claim 5, characterized in that: The oxidant in step (2) is ammonium persulfate, and the mass volumes of the pyrrole, multi-walled carbon nanotubes, dispersion containing precious metal nanoparticles, steric stabilizer, oxidant and acidic medium are 2-4g: 0.004-0.01g: 1.25-10ml: 10-20g: 40-70g: 4-10ml, and the in-situ polymerization is carried out in an ice-water bath.
7. A composite copper foil for circuits, characterized in that: The composite copper foil comprises the polypyrrole coating according to any one of claims 1-2 or a polypyrrole coating prepared by the preparation method according to any one of claims 3-6, a polymer base film, a cured resin coating, a precious metal colloid coating and a copper layer; one side or both sides of the polymer base film are the cured resin coating, the precious metal colloid coating, the polypyrrole coating and the copper layer, and the surface of the polypyrrole coating away from the polymer base film is the copper layer.
8. A method for preparing a composite copper foil as claimed in claim 7, characterized in that: The steps include: (1) first coating the surface of the polymer base film with a light-curing resin coating, and then immersing it in the polypyrrole coating according to any one of claims 1 to 2 or the polypyrrole coating prepared by the preparation method according to any one of claims 3 to 6 to obtain a polymer composite film; (2) The polymer composite film is then immersed in an alkaline chemical copper plating solution for copper plating to obtain a composite copper foil.
9. The preparation method according to claim 8, characterized in that: The polymer base film in step (1) is selected from any one of polyimide film, polypropylene film, polyvinyl chloride film, polystyrene film, polyphenylene sulfide film, polybutylene terephthalate film, poly(p-phenylene terephthalamide), polypropylene film, butadiene-styrene copolymer film, polyimide film, imide film, polyethylene terephthalate film, polyethylene PE film, polypropylene PP film, polyethylene diethyl phthalate PET film and poly(dibutyl phthalate) PBT film, and the coating dry weight of the coating is 0.1-6 g / cm 3 The polymer composite film needs to be exposed and cured, and the thickness of the polymer composite film is 60-100nm.
10. The preparation method according to claim 8, characterized in that: The alkaline chemical copper plating solution in step (2) is composed of copper sulfate with a concentration of 5-10 g / L, sodium hypophosphite with a concentration of 10-30 g / L, dimethylaminoborane with a concentration of 0.5-2.0 g / L and disodium ethylenediaminetetraacetate with a concentration of 15-20 g / L. The copper plating temperature is 80-100° C. and the copper plating time is 1-2 h.
Citation Information
Patent Citations
Method for preparing polypyrrole / multi-wall carbon nano tube composite material with core-shell structure
CN102516539A
Method and device for preparing carbon nanotube / conductive polymer composite materials
CN109545574A
Flexible electric heating film heating layer and preparation method thereof
CN112566290A
Flexible modified polymer composite conductive film and preparation method thereof
CN116259439A
Composite copper foil for flexible circuit as well as preparation method and application of composite copper foil
CN117777522A
